OP0092 The Arrhythmic Burden in Systemic Sclerosis: Ventricular Ectopic Beat Rate Correlates with Cardiac Damage and Bad Prognosis. (10th June 2014) - De Luca, G.; Bosello, S.; Parisi, F.; Berardi, G.; Rucco, M.; Canestrari, G.; Ferraccioli, G.
Abstract : Background: Primary heart involvement is a relevant prognostic determinant in Systemic Sclerosis (SSc) and, together with pulmonary disease, is the leading cause of death in these patients. Arrhytmhias are a frequent event and portend a bad prognosis, accounting alone for the 6% of total deaths. Objectives: The aim of our study was to define the role of EKG-Holter in the characterization of arrhythmic burden in SSc-patients and in the identification of patients with poor prognosis. Methods: Seventy-two consecutive SSc-patients (median age:55.0 years, range 23-81 years; median disease duration: 6.0years, range:0.3-32; diffuse disease: 55.6%; anti-Scl70 positivity: 41.7%), with signs and or symptoms suggestive of cardiac involvement (i.e. dyspnoea, palpitations and/or rise of cardiac enzymes) underwent 24h EKG-Holter from 2008 to 2013. A complete assessment of disease characteristics and organ involvement was also performed. During the same period the occurrence of any cardiac complication and death was recorded. Results: Major EKG-holter modifications (presence of ventricular or supraventricular ectopic beats, ventricular and/or supraventricular tachycardia, rhythm alterations) were present in 55.6% of patients. The majority of patients (94.4%) were on sinus rhythm, while atrial fibrillation or idioventricular rhythm were identifiable only in 2 patients. The mean cardiac frequency was 78.0±11.4 bpm, with a maximum frequency of 131.0±28.7 bpm and a minimum of 54.9±11.3 bpm. Right bundle brunch block was present in 20.8% and ventricular ectopic beats (VEBs) >1000/24h in 19 patients (26.4%); VEBs were classified as polymorphic in 7 patients (9.7%). The mean number of VEBs was strikingly higher (1611.9±4678.3). Supraventricular ectopic beats (SVEBs) >1000/24h were also frequent (16.7%).Twelve patients (16.7%) presented during 24-h evalutation a supraventricular tachycardia and 7 patients (9.7%) a non-sustained ventricular tachycardia (NSVT). The number of VEBs and SVEBs correlated with troponin T levels (R=0.26, R=0.36 respectively, p<0.04 for both correlations). Furthermore, the number of VEBs directly correlated with modified Rodnan skin score (R=0.24, p=0.04) and inversely correlated with ejection fraction (R=-0.39, p=0.001). During the observational period of 5 years, 6 deaths related to the sclerodermic disease progression occurred; five patients (6.9%) died for sudden cardiac death and all of them had VEBs >1000/24h. Dead patients presented higher number of VEBs and SVEBs (p<0.001 for both comparisons), higher levels of troponin T, CPK-MB and NT-proBNP (p<0.001 for all comparisons), and higher disease activity index (p<0.008). On ROC curve, VEBs >1125 showed a sensitivity of 83.3% and a specificity of 92.5% to predict SSc-cardiac related death (AUROC=0.85, CI=0.70-0.98). Patients with VEBS>1125 more frequently presented an increase of cardiac enzymes, right bundle brunch block and episodes of NSVT (p<0.001 for all comparisons) and had higher severity index score. Conclusions: Our data reveal that arrhythmyas are frequent in the course of scleroderma disease and the presence of VEBS>1125/24h correlates with cardiac damage and poor prognosis. The presence of EKG-Holter modifications need to be routinely investigated in SSc patients in order to identify those with a bad prognosis. Disclosure of Interest: None declared DOI: 10.1136/annrheumdis-2014-eular.4462